PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP NEGERI 41 PADANG - Suraiya, Suraiya; Hafrison, Mohamad; Amir, Amril; Hasnul Ulya, Ridha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study has three objectives. The three objectives are as follows. First, to describe the writing skills of poetry texts of class VIII students of SMP Negeri 41 Padang using the project based learning model assisted by audiovisual media. Second, to describe the writing skills of poetry texts of class VIII students of SMP Negeri 41 Padang using the conventional model. Third, to analyze the effect of the project based learning model assisted by audiovisual media on the writing skills of poetry texts of class VIII students of SMP Negeri 41 Padang. This type of research is quantitative research using the quasi-experimental design method. The research design in this study is a posttest only control group design. The sample in this study was 25 people in the experimental class while 23 people in the control class. The sampling technique was purposive sampling.